ANALYSIS OF ONLINE PURCHASE INTENTION USING SCARCITY AND LIKING AS THE PERSUASION MARKETING STRATEGIES - Patricia Vania; Lila Maria Kaban (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
Customers shopping behaviors have altered because of technological advancement and widespread of internet access. The rise in online sales presents both opportunities and challenges for many e-commerce companies. To successfully increase the customers’ purchase intention, it is important to implement persuasion marketing strategies especially in the online environment, together with other traditional marketing techniques available. The goal of this study is to determine which technique, between Scarcity Tactics and Liking Tactics, has more impact on customers’ Purchase Intention. Zalora Indonesia, as one of the leaders in fashion, beauty, home and lifestyle e-commerce, is chosen to be the research object. Scarcity Tactics and Liking Tactics are the independent variables used in this study, with customers’ Purchase Intention as the dependent variable. Quantitative method using a causal strategy, with an online questionnaire has been delivered to 120 Zalora Indonesia buyers. According to the findings of this research, customers who buy online have the tendency to do purchases when Zalora Indonesia uses Scarcity Tactics and Liking Tactics in its marketing approach. Scarcity Tactics, however, has more influence on online Purchase Intention, whereas Liking Tactics has a promising but insignificant impact. Both Scarcity Tactics and Liking Tactics show influences in customers’ Purchase Intention as much as 60.2%.